La interacción tutor-estudiante en ámbitos de educación a distancia - Abarca Amador, Yohanna (2014)
Througout history distance education programs have adapted to the increasing social demands of a labor force with superior levels of training and education. Likewise, the role of the on-line tutor has evolved from an isolated figure with little impact on learners’ academic life to a facilitator and motivator not only in terms of methododogical but also technological issues required by distance education today. In order to play this role efficiently the distance tutor relies on an array of communication tools, both synchronic and asynchronic, in the Internet. Therefore, the tutorial role on line calls for new abilities and duties which facilitate the distant learner’s successful fulfillment of the proposed academic objectives.